Co-housing design. New qualities through new housing collaborations. - Tummers, Lidewij (vdf Hochschulverl., 2018)
The text aims at an overview of the contemporary trend in Cohousing - an umbrella-term for resident-led housing initiatives -, which can be considered an important recent development in many European housing markets. The author presents data from a comparative study of Dutch and Swiss projects, trying to shed further ligt on general and specific aspects of such projects. Cohousing advocates inclusiveness and sustainability and points the way to new models of design as well as of cocreation processes.
Keywords: Wohnform; Wohnen; Gemeinschaftsnutzung; Gemeinschaftseinrichtung; Partizipation; Cohousing; Gemeinschaftsfläche; Nachhaltigkeit; Fallbeispiel